2016
DOI: 10.1103/physreva.93.063609
|View full text |Cite
|
Sign up to set email alerts
|

Producing directed migration with correlated atoms in a tilted ac-driven lattice

Abstract: The correlated atoms in a tilted optical lattice driven by an ac-field are studied within the Hubbard model. By making use of both the photon-assisted tunneling and coherent destructive tunneling effects, we can move a pair of strongly correlated atoms in the lattice via manipulating the global amplitude of the driving field. We propose a scheme of creating entanglement between the particlepair and a single particle through interacting oscillations. Our model may provide a new building block for investigating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…We also expect possible applications of the scheme to the preparation of robust quantum entangled states and to the quantum information processing. In fact, a double-well trapped many-boson system can be divided into two subsystems A and B and the corresponding bipartite entangled states have been investigated 19 21 , which can be used to encode the qubit 22 . Noticing the indistinguishability of identical bosons, we can divide the considered three-boson system into the subsystem A of a single-boson and subsystem B of a pair-boson.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also expect possible applications of the scheme to the preparation of robust quantum entangled states and to the quantum information processing. In fact, a double-well trapped many-boson system can be divided into two subsystems A and B and the corresponding bipartite entangled states have been investigated 19 21 , which can be used to encode the qubit 22 . Noticing the indistinguishability of identical bosons, we can divide the considered three-boson system into the subsystem A of a single-boson and subsystem B of a pair-boson.…”
Section: Discussionmentioning
confidence: 99%
“…A double-well trapped many-boson system or an atomic Bose-Einstein condensates (BEC) in two different hyperfine states trapped in a single trap can be treated as a bipartite system of two modes 19 21 . The bipartite entangled states in such a system have been investigated, which can be used to encode the qubit 22 . As a maximal bipartite entangled state the NOON state has also been widely studied 22 , 23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high tunability of optical lattices also provides an ideal platform for periodically driven systems which lead to various effective Hamiltonians based on the Floquet theory [11]. The dynamical localization (DL) [12,13], photonassisted tunneling [14] as well as coherent destructive tunneling (CDT) [15][16][17][18] were utilized to induce the superfluid to Mott insulator transition [19][20][21], quantum control of selective tunneling [22,23], directed migration of atoms or the creation of quantum entanglement [24,25], etc.…”
Section: Introductionmentioning
confidence: 99%
“…In recent works, we have proposed several ways to manipulate directed motion in optical lattices by doubly driving the optical lattices or tilting the lattice with a single AC field [24,25]. In [22], the authors suggested the realization of directed motion of a Bose condensate in a bipartite superlattice by making use of the CDT with a modulated driving field.…”
Section: Introductionmentioning
confidence: 99%